CHALLENGES AND PERSPECTIVES FOR POPULATION AGING: A BRAZIL-ARGENTINA COMPARATIVE ANALYSIS - Cristina Barboza da Silva Morais, Andréia; Darc Ferreira da Silva, Joana; Costa Rodrigues da Silva, Kênya; da Silva Farias, Roseane; Erika Ferro Ramalho Nobre, Sheila; Maria Marchi, Silvana (Health and Society, 2024)
This article examines the complexity of population aging, highlighting the social, economic and political dynamics that shape the experience of older people. Through a comparative approach between Brazil and Argentina, we explore public policies, cultural changes and the challenges faced by this growing part of society. Based on authors such as Austerlitz, Sen and Palacios, the study addresses the need for public investments, the importance of recognizing the rights of the elderly and transformations in care models. By analyzing specific legislation, such as the Statute of the Elderly in Brazil and the Inter-American Convention on the Human Rights of the Elderly in Argentina, we highlight advances and challenges. We conclude by highlighting the urgency of a comprehensive approach that goes beyond standardization, involving the effective implementation of policies to guarantee a dignified quality of life for the elderly population.